CCNB1 and AURKA are critical genes for prostate cancer progression and castration-resistant prostate cancer resistant to vinblastine - Chen, Xi; Ma, Junjie; Wang, Xin’an; Zi, Tong; Qian, Duocheng; Li, Chao; Xu, Chengdang (Frontiers in Endocrinology, 2022)
Background: Prostate cancer (PCa) is a common malignancy occurring in men. As both an endocrine and gonadal organ, prostate is closely correlated with androgen. So, androgen deprivation therapy (ADT) is effective for treating PCa. However, patients will develop castration-resistant prostate cancer (CRPC) stage after ADT. Many other treatments for CRPC exist, including chemotherapy. Vinblastine, a chemotherapeutic drug, is used to treat CRPC. However, patients will develop resistance to vinblastine. Genetic alterations have been speculated to play a critical role in CRPC resistance to vinblastine; however, its mechanism remains unclear. Methods: Various databases, such as Gene Expression Omnibus (GEO), The Cancer Genome Atlas (TCGA) and Chinese Prostate Cancer Genome and Epigenome Atlas (CPGEA), were used to collect the RNA-sequence data of PCa and CRPC patients and vinblastine-resistant PCa cells. Using online tools, Metascape and TIMER, the pathways and immune infiltration associated with vinblastine resistance-related genes in PCa were analyzed. The function of these genes was verified in clinical samples and CRPC cells. Results: Using GSE81277 dataset, we collected the RNA-sequence data of vinblastine sensitive and resistant LNCaP cells and found nine genes (CDC20, LRRFIP1, CCNB1, GPSM2, AURKA, EBLN2, CCDC150, CENPA and TROAP) that correlated with vinblastine resistance. Furthermore, CCNB1, GPSM2 and AURKA were differently expressed between normal prostate and PCa tissues, even influencing PCa progression. The GSE35988 dataset revealed that CCNB1 and AURKA were upregulated in PCa and CRPC samples. Various genes were also found to affect the survival status of PCa patients based on TCGA. These genes were also related to immune cell infiltration. Finally, we verified the function of CCNB1 and AURKA and observed that they were upregulated in PCa and CRPC clinical samples and increased the sensitivity of CRPC cells to vinblastine. Conclusion: CCNB1 and AURKA are central to CRPC resistance to vinblastine and affect PCa progression.